2018
DOI: 10.1111/codi.14108
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic surgery is effective and safe after endoscopic polypectomy of potentially malignant rectal polyps with questionable margins

Abstract: After endoscopic polypectomy of malignant rectal polyps with questionable margins, the presence of residual lesion in the pathology study of transanal resection specimens is high. TEM with full-thickness resection of these lesions is an appropriate treatment, allowing disease control and achieving minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…In our series, in half of the polypectomies the margin of the cancer excision was either involved or indeterminate, yet none of these (0/32) had residual cancer at TEM, consistent with Junginger et al It has been suggested that after polypectomy with unsatisfactory margins, local excision should be done as it is a minor procedure and removes the risk of recurrence [4]. It is certainly debatable whether TEM (or other means of local excision) is a minor procedure, and there is a recognized morbidity.…”
Section: Discussion and Con Clus Ionssupporting
confidence: 89%
See 1 more Smart Citation
“…In our series, in half of the polypectomies the margin of the cancer excision was either involved or indeterminate, yet none of these (0/32) had residual cancer at TEM, consistent with Junginger et al It has been suggested that after polypectomy with unsatisfactory margins, local excision should be done as it is a minor procedure and removes the risk of recurrence [4]. It is certainly debatable whether TEM (or other means of local excision) is a minor procedure, and there is a recognized morbidity.…”
Section: Discussion and Con Clus Ionssupporting
confidence: 89%
“…The optimal management of these polyp cancers is unclear, particularly if the polyp was fragmented during removal and completeness of removal cannot be determined.Many can be considered cured by the simple polypectomy; however, there is a recognized small group that will develop extensive recurrent disease [3]. Completion local excision of the polyp stalk or scar has been advocated, but the benefit of this is unclear [4][5][6]. A review of the management of rectal polyps [7] notes the difficulties in decision-making after polypectomy when clear prognostic information about depth of invasion and margin clearance is not available due to fragmentation of the specimen or artefacts due to polypectomy technique.…”
mentioning
confidence: 99%
“…Serra‐Aracil et al . performed an observational study that included consecutive patients who underwent a local resection by means of TEM following endoscopic polypectomy. This study included 36 patients with a low risk adenocarcinoma with potentially involved margins.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, TES serves as a valuable diagnostic tool following incomplete polypectomy of unsuspected malignant pT1 polyps. Across various studies, TEM is reported to identify residual adenomatous and/or adenocarcinoma in up to 14.8 to 70% 20 21 22 23 of cases. When full-thickness TEM excision is performed for a residual pT1 tumor deemed low risk for nodal metastasis based on histologic review and/or staging with endoscopic ultrasound and/or pelvic MRI, TEM achieves good local control with acceptable local recurrence rates (see later section).…”
Section: Local Excision Of Early Rectal Cancer: Techniques Selection ...mentioning
confidence: 99%
“…In such event, additional attempt at curative local excision using full-thickness TAE or TES may be considered, if no high-risk histopathological features are identified that warrant an oncologic resection. 20 21 22 23 However, if ESD was performed for an unsuspected malignant polyp, R0 resection might have been achieved if the focus of invasion was limited to the upper submucosal layer. If pathology review of the specimen determines that deep and lateral margins are conclusively negative, and if no adverse risk factors are identified to indicate a high risk of lymph node metastasis, ESD can, in some cases, achieve curative resection of superficial T1 rectal tumors.…”
Section: Local Excision Of Early Rectal Cancer: Techniques Selection ...mentioning
confidence: 99%